PENGARUH EKSPEKTASI PENDAPATAN, PENGETAHUAN KEWIRAUSAHAAN DAN MINDSET WIRAUSAHA TERHADAP MINAT BERWIRAUSAHA PEGAWAI NEGERI SIPIL BADAN PENGELOLAAN KEUANGAN DAN PENDAPATAN DAERAH PROVINSI JAMBI - Rosadi, Ichsan; Yacob, Syahmardi; Lubis, Tona Aurora (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study investigates the influence of income expectations, entrepreneurial knowledge, and entrepreneurial mindset on entrepreneurial intention among civil servants at the Regional Revenue and Financial Management Agency (BPKPD) of Jambi Province, Indonesia. Employing a quantitative approach with a descriptive-verificative design, the research utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis, processed using SmartPLS 3.0. Data were collected through structured questionnaires from a purposive sample of 156 respondents, determined using Slovin's formula from a total population of 296. The findings reveal that all three independent variables exert a statistically significant and positive effect on entrepreneurial intention. Income expectation (β = 0.302; t = 3.161; p < 0.01), entrepreneurial knowledge (β = 0.937; t = 9.754; p < 0.001), and entrepreneurial mindset (β = 0.347; t = 3.079; p < 0.01) significantly contribute to shaping entrepreneurial interest among civil servants. The model demonstrates a high explanatory power with an R-squared value of 0.976, indicating that 97.6% of the variance in entrepreneurial intention is explained by the model. These results underscore the importance of fostering entrepreneurial literacy, realistic income expectations, and a proactive entrepreneurial mindset in encouraging civil servant engagement in entrepreneurship. The study contributes to the literature by addressing a research gap concerning public sector entrepreneurship and provides practical implications for policy formulation aimed at promoting entrepreneurial development among state employees.